SUCCESSION OF BACTERIA ATTACHED TO EVERGREEN OAK LEAF SURFACES (EUROPEAN JOURNAL OF SOIL BIOLOGY, 1993)
Heterotrophic attached bacteria were isolated from evergreen oak leaf surfaces (Quercus ilex L.) on both phylloplane and litter at each season during one year. Few epiphytic bacteria were recovered from the phylloplane (18 %) in comparison with the litter. The data derived from the 324 strains were subjected to cluster analysis. The taxonomic structure displayed 44 phenetic groups. The bacterial communities on leaf surfaces belonged mainly to two genera: Bacillus (31 %), present on both phylloplane and litter, and Pseudomonas (35 %) present only on the litter. Some communities of Bacillus were able to degrade structural chemical components of the leaf, such as pectins or lignin monomers. The Bacillus isolates were generally more numerous in spring and in summer, i.e. during the warm seasons, whereas Pseudomonas predominated in autumn and winter. In vitro measurements of strains growth rates showed moreover that Bacillus strains grew better at 40-degrees-C than Pseudomonas strains. A climate-related factor, namely temperature, has therefore a great influence on the natural selection process of these communities. Another seasonal succession was observed, involving two genera: Xanthomonas predominant in winter and Lactobacillus in summer, as well as the Enterobacteriaceae family in autumn.